Secondary magnetite in ancient zircon precludes analysis of a Hadean geodynamo - Tang, F.; Taylor, Richard; Einsle, J.; Borlina, C.; Fu, R.; Weiss, B.; Williams, H.; Williams, W.; Nagy, L.; Midgley, P.; Lima, E.; Bell, E.; et al. (National Academy of Sciences, 2019)
Zircon crystals from the Jack Hills, Western Australia, are one of the few surviving mineralogical records of Earth’s first 500 million years and have been proposed to contain a paleomagnetic record of the Hadean geodynamo. A prerequisite for the preservation of Hadean magnetization is the presence of primary magnetic inclusions within pristine igneous zircon. To date no images of the magnetic recorders within ancient zircon have been presented. Here we use high-resolution transmission electron microscopy to demonstrate that all observed inclusions are secondary features formed via two distinct mechanisms. Magnetite is produced via a pipe-diffusion mechanism whereby iron diffuses into radiation-damaged zircon along the cores of dislocations and is precipitated inside nanopores and also during low-temperature recrystallization of radiation-damaged zircon in the presence of an aqueous fluid. Although these magnetites can be recognized as secondary using transmission electron microscopy, they otherwise occur in regions that are indistinguishable from pristine igneous zircon and carry remanent magnetization that postdates the crystallization age by at least several hundred million years. Without microscopic evidence ruling out secondary magnetite, the paleomagnetic case for a Hadean–Eoarchean geodynamo cannot yet been made.